2020
DOI: 10.1111/fare.12490
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Abuse as a Mediator Between Insecure Attachment Orientations and Relationship Satisfaction

Abstract: Objective To test the mediating effect of perpetrating psychological abuse between insecure attachment orientations and relationship satisfaction among couples. Method The mediating effect of psychological abuse between attachment orientation and relationship satisfaction was investigated among 128 couples (N = 256 participants) in enduring relationships using the actor–partner interdependence model. Results Actor effects indicated men and women higher in anxious attachment perpetrate more psychological abuse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Regarding relationship factors, studies that focus on the association between relationship satisfaction and IPV suggest that lower relationship satisfaction is associated with higher rates of IPV in couple relationships (Shortt et al, 2013). Higher attachment anxiety has also been associated with higher rates of IPV perpetration among both men and women (Gewirtz‐Meydan & Finzi‐Dottan, 2021). Individuals high in attachment anxiety consistently seek the approval of others and are extremely fearful of rejection or abandonment, which, through demands for reassurance and closeness, may result in IPV perpetration (Gewirtz‐Meydan & Finzi‐Dottan, 2021).…”
Section: Conflict Management Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding relationship factors, studies that focus on the association between relationship satisfaction and IPV suggest that lower relationship satisfaction is associated with higher rates of IPV in couple relationships (Shortt et al, 2013). Higher attachment anxiety has also been associated with higher rates of IPV perpetration among both men and women (Gewirtz‐Meydan & Finzi‐Dottan, 2021). Individuals high in attachment anxiety consistently seek the approval of others and are extremely fearful of rejection or abandonment, which, through demands for reassurance and closeness, may result in IPV perpetration (Gewirtz‐Meydan & Finzi‐Dottan, 2021).…”
Section: Conflict Management Behaviorsmentioning
confidence: 99%
“…Higher attachment anxiety has also been associated with higher rates of IPV perpetration among both men and women (Gewirtz‐Meydan & Finzi‐Dottan, 2021). Individuals high in attachment anxiety consistently seek the approval of others and are extremely fearful of rejection or abandonment, which, through demands for reassurance and closeness, may result in IPV perpetration (Gewirtz‐Meydan & Finzi‐Dottan, 2021).…”
Section: Conflict Management Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These dysfunctional behaviors, in addition to being potentially harmful to their partner's relationship satisfaction, are known to increase the risk of perpetrating and sustaining IPV (Mikulincer & Shaver, 2016 ). Studies have indeed documented higher relationship dissatisfaction in couples who report IPV (Gewirtz & Finzi, 2020 ; Panuzio & DiLillo, 2010 ; Spencer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of these correlates can help clinicians better identify when one may be at risk for IPV within their relationship. Due to the high prevalence of IPV and its association with a variety of issues, such as relationship dissatisfaction (Gewirtz-Meydan & Finzi-Dottan, 2021) and mental health problems (Rogers & Follingstad, 2014) that may lead someone to seeking services, it is essential that health professionals are aware of correlates of IPV and related assessment and treatment considerations. Fitzgerald (2020) found that women are more likely to report emotional IPV compared to physical and sexual IPV, making it critical for assessment purposes.…”
mentioning
confidence: 99%